Postmodernism and loss : evocations of life amidst loss in Vladimir Nabokov's Lolita and Pale Fire. - Kwok, Michelle Jia Yu. (2013)
This essay will explore the treatment of loss and grief in Vladimir Nabokov's novels Pale Fire and Lolita. I will argue that the narrators of Pale Fire and Lolita grapple with loss and grief through language. Both novels use language to reveal the myriad possibilities of life, exploring alternative realities such as fantasy worlds and even the afterlife. These creative attempts to deal with loss result in evocations of life amidst loss. Such evocations, coupled with the invigorative qualities of literary recreation, consequently help the narrators alleviate their feelings of pain and grief accompanying loss.